Analisis Angka Seksio Caesarea di RSUP Dr. Sardjito Yogyakarta Tahun 2009-2013 - Dameria, Netty Katrina; Dasuki, Djaswadi; Siswishanto, Rukmono (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: Caesarean section is a procedure to reduce maternal and perinatal mortality and morbidity. The caesarean section rate is continuously uprising in the last 3 decades. However, the increasing rate, especially in low risk women, may compromise maternal and perinatal outcome. In 1985, WHO recommended that optimal national caesarean rates should be in the range of 5% to 10% and the rate above 15% might be less benefits. Previous study conducted in DR Sardjito hospital reported caesarean section rate in 1996 was 13.38%, while in 2001 was 18.39%. In national level, based on Indonesia Basic Health Survey 2010, caesarean section rate was 10.8%. Therefore, in this study we analyzed the rate of Caesarean section performed in DR Sardjito hospital, and studied whether the operations occurred in high-risk group or low-risk group.Objective: To compare the rate of caesarean section between high-risk group and low-risk group in DR Sardjito hospitalMethod: Retrospective cohortResult and Discussion: Participants of this study were 7821 patients undergoing labor at RSUP DR Sardjito in 2009-2013. Among them, 3152 patients underwent caesarean section and 4669 patients underwent vaginal delivery. There was an increasing in the overall caesarean section rate of 38,7% in 2009 to 43% in 2013. T-test found the presence of significant differences between the caesarean section rate of high-risk group and low-risk group in 2009-2013 (p<0.05) with a mean difference was 28.5 (20.2-36.8). Caesarean section rate of high-risk group was significantly higher than the low-risk group (p<0.05).Conclusion: There was a difference in caesarean section rate of high-risk group compared to low-risk group. Caesarean section rate in high-risk group was significantly higher than in the low-risk group.Keywords: caesarean section rate, caesarean section, low-risk group, high- risk group